COUROUPITA GUIANENSIS: THE RESERVOIR OF MEDICINAL COMPOUNDS OF HUMAN WELFARE - Jasmine S, Famina; Moorthi P, Vinayaga (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Medicinal plants play a role in the traditional form of providing relief to several diseases. Couroupita guianensis is also a type of medicinal plant which has antibacterial, antimycobacterial, antimicrobial, antioxidant, antitumor, antiulcer, antinociceptive, anthelmintic, antifertility, and antifungal activities. The chemical constituent of C. guianensis such as indirubin serves as an antibacterial and antifungal agent because it particularly cures fungal diseases. It is active for the treatment of chronic myelocytic leukemia. The extract of isatin from the flower of C. guianensis is also a chemical component that has been used as prophylactic agent, prevents free radial-induced cancer, acts as a chemotherapeutic agent to kill cancer cells, and it has antioxidant (act as major defense) and anticancer activities against human promylocytic leukemia 60 cells. The extract of chloroform of fruit of C. guianensis shows good antimicrobial activity but low antimycobacterial activity. The plant extract of C. guianensis is equipotent to standard drugs such as paracetamol in its analgesic activity and indomethacin in its anti-inflammatory activity. Keywords: Couroupita quianensis, Antibacterial activity, Anti tumor activity, Antioxidant activity, Anti biofil.